Combination of steam explosion pretreatment and anaerobic alkalization treatment to improve enzymatic hydrolysis of Hippophae rhamnoides. (October 2019) - He, Liwen; Wang, Cheng; Shi, Honghui; Zhou, Wei; Zhang, Qing; Chen, Xiaoyang
Highlights: Steam explosion (SE) at 1.5 MPa for 20 min was optimum for hippophae. 2% CaO alkalization (CA) decreased lignocellulose of hippophae in solid state. SE and CA was first used in sequence to overcome lignocellulosic recalcitrance. Saccharification was enhanced by 355%, 301% and 400% via SE, CA and SE-CA. Abstract: The optimum condition of steam explosion pretreatment was screened for hippophae, and anaerobic calcium oxide (CaO) alkalization was further used to improve its enzymatic hydrolysis . Steam-exploded hippophae reached the lowest pH value (4.01) and the maximal hemicellulose removal (77.16%) at pressure 1.5 MPa and residence time 20 min. Lignocellulosic fractions of hippophae was remarkably reduced by CaO alkalization or steam explosion treatment, and enzymatic sugar yield was increased from 66 mg/g DM (untreated material) to 270 and 300 mg/g DM, respectively. The sequent pretreatment of steam explosion and CaO alkalization achieved a sugar yield of 330 mg/g DM, where 2% CaO loading rate was high enough. Besides, SEM, FTIR, and XRD analyses validated structural and physicochemical changes of hippophae. In conclusion, the sequent pretreatment of steam explosion at pressure 1.5 MPa for 20 min and anaerobic CaO alkalization at 2% loading rate could remarkably improve enzymatic hydrolysis of hippophae.